Protein fingerprinting of Staphylococcus species by capillary electrophoresis with on-capillary derivatization and laser-induced fluorescence detection - Veledo, Maria Teresa; Peláez Lorenzo, Cristina; González, Ramon; de Frutos, Mercedes; Diez Masa, Jose Carlos (My University, 2009)
Capillary electrophoresis (CE) coupled with laser-induced fluorescence detection (LIF) has allowed to obtain protein fingerprints, which have demonstrated to be useful in microorganisms characterization. In this work, protein fingerprints of two species of Staphylococcus grown in different culture media and submitted to temperature and nitrosative stress were studied by CE-LIF. After the growth of the bacteria, protein extracts were obtained by cell lysis using sonication. The water-soluble fraction of these lysates was derivatized on-capillary with a fluorogenic dye, 3-(2-furoyl)quinoline-2-carboxaldehyde. The flu orescent products were analyzed by CE using phosphate buffer containing submicellar concentrations of sodium pentanesulfate and detected by LIF. Different protein fingerprints were obtained depending on the bacterial specie studied, indicating the usefulness of this method for the identification of differ ent species of the same bacterial genus. It was also demonstrated that the CE protein fingerprints were dependent on the culture conditions, such as growth medium, or on stressing conditions, such as heat shock or nitrosative stress.